Inventory Of Greenhouse Gas Emissions From Rice Paddy Farming Activities In The Regency of Karawang - Baitierachmah, Silfya; Adzillah, M.T., Ing. Wilma Nurrul; Fauzie, S.T., M.Sc., Ph.D., Azis Kemal (Universitas Tanjungpura, 2025)
The phenomenon of climate change has become a significant global issue, that is contributing to the phenomenon of global warming. One of the fields that contribute to greenhouse gas emissions is agriculture. Karawang Regency is dubbed as the rice granary of West Java because it is one of the regions that contribute to the national rice demand. Karawang Regency has not conducted a greenhouse gas emissions inventory, but the impact of climate change has been felt by the people of Karawang Regency, for example, rising sea levels and increasing daily temperatures. Research is needed that focuses on the inventory of greenhouse gas emissions in wet-rice farming. The purpose of this research is to calculate and map greenhouse gas emissions from rice paddy farming activities in Karawang Regency. The method in calculating this refers to the 2006 IPCC guidelines while the mapping uses QGIS software. The greenhouse gas emission burden of wet-rice farming activities in Karawang Regency was found to be 191.47 Gg CO2-eq/year, with Cilebar District contributing the most emissions at 37.53 Gg CO2-eq/year. After mapping the calculation results, Tirtajaya District, Cilebar District and Pedes District have a darker color than other districts on the map.